The Impact of Psychosocial Factors on the Human—Pet Bond: Insights from Cat and Dog Owners - Garikoitz Azkona (Animals, 2025)
This study underscores how perceived social support, loneliness, and mental well-being shape the emotional bonds that Spanish cat and dog owners form with their pets. A total of 298 participants completed an online survey, including 109 cat owners (36.5%) and 189 dog owners (63.4%). Standardized and validated instruments were used: the Medical Outcomes Study Social Support Survey (MOS-SSS), the UCLA Loneliness Scale, the Warwick–Edinburgh Mental Well-Being Scale (WEMWBS), and the Lexington Attachment to Pets Scale (LAPS). The results confirmed that the attachment to dogs tends to be stronger than to cats, with demographic factors such as gender and age also playing a significant role in the attachment levels. While psychosocial variables did not directly predict the overall attachment scores, lower perceived social support was significantly associated with higher scores on the person substitution subscale among dog owners, indicating that dogs may serve as emotional substitutes for human companionship in socially vulnerable individuals. No comparable association was found among cat owners. These findings highlight species-specific differences in the human–pet bond and emphasize the multifaceted nature of attachment. This study underscores the importance of considering both demographic and psychosocial factors to better understand how pets contribute to human emotional well-being.